2020
DOI: 10.1111/his.14039
|View full text |Cite
|
Sign up to set email alerts
|

Histological grading of ovarian mucinous carcinoma – an outcome‐based analysis of traditional and novel systems

Abstract: AimsGrading of primary ovarian mucinous carcinoma (OMC) is inconsistent among practices. The International Collaboration on Cancer Reporting recommends grading OMC using the International Federation of Gynecology and Obstetrics (FIGO) system for endometrial endometrioid carcinoma, when needed. The growth pattern (expansile versus infiltrative), a known prognostic variable in OMC, is not considered in any grading system. We herein analysed the prognostic value of various grading methods in a well‐annotated coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(50 citation statements)
references
References 17 publications
6
42
2
Order By: Relevance
“…For this reason, the reported prognostic significance of infiltrative invasion in primary ovarian mucinous carcinomas in older studies, where misdiagnosis of metastasis to the ovary as primary ovarian carcinoma could have occurred, has been criticised. Nonetheless, the same prognostic association has been found in recent series which have been more strictly curated using gross and microscopic pathology, immunohistochemistry and/or patient follow‐up data to confirm primary ovarian origin 63–65 …”
Section: Mucinous Carcinomasupporting
confidence: 60%
See 1 more Smart Citation
“…For this reason, the reported prognostic significance of infiltrative invasion in primary ovarian mucinous carcinomas in older studies, where misdiagnosis of metastasis to the ovary as primary ovarian carcinoma could have occurred, has been criticised. Nonetheless, the same prognostic association has been found in recent series which have been more strictly curated using gross and microscopic pathology, immunohistochemistry and/or patient follow‐up data to confirm primary ovarian origin 63–65 …”
Section: Mucinous Carcinomasupporting
confidence: 60%
“…70 Based on the prognostic value of the type of invasion in mucinous carcinomas discussed above, Busca et al proposed an alternative grading system based on the presence and amount of infiltrative growth in their study of 52 ovarian mucinous carcinomas. 65 The system classified tumours as low-grade (expansile invasion or infiltrative invasion representing ≤10% of the tumour) and high-grade (infiltrative invasion in >10% of the tumour). This grading correlated with disease-free survival.…”
Section: Histological Gradingmentioning
confidence: 99%
“…also found that grade 3 tumors were an independent poor prognostic factor in terms of PFS 22 . However, it remains controversial whether grade correlates with unfavorable survival outcomes in mucinous carcinomas 23 . Moreover, the grading system for ovarian mucinous carcinomasis globally inconsistent 23 .Busca et al compared two widely used grading systems: the International Federation of Gynecology and Obstetrics (FIGO) system 24 , which was the same grading system used for endometrioid carcinoma, and the Silverberg grading system 25 .…”
Section: Second Malignancies Among Women With Early-stage Eoc Who Fssmentioning
confidence: 99%
“…However, it remains controversial whether grade correlates with unfavorable survival outcomes in mucinous carcinomas 23 . Moreover, the grading system for ovarian mucinous carcinomasis globally inconsistent 23 .Busca et al compared two widely used grading systems: the International Federation of Gynecology and Obstetrics (FIGO) system 24 , which was the same grading system used for endometrioid carcinoma, and the Silverberg grading system 25 . They found that only the Silverberg grading system appeared to correlate with outcome in cases of mucinous carcinoma 23 .…”
Section: Second Malignancies Among Women With Early-stage Eoc Who Fssmentioning
confidence: 99%
See 1 more Smart Citation